INOVASI TEKNOLOGI VARIETAS UNGGUL BARU (VUB) MENINGKATKAN PRODUKTIVITAS PADI DAN PENDAPATAN PETANI DI LAHAN RAWA LEBAK - Suparwoto, Suparwoto; Waluyo, Waluyo (Publikasi Penelitian Terapan dan Kebijakan, 2011)
Superior new technology innovation variety enhance rice productivity and income farmers in swampland. Efforts to increase rice productivity and efficiency of farming continue to be done to meet the food security and increase farmers' income. Variety is one component of superior technology that has a real role in improving production and quality of agricultural commodities. Contribution of superior varieties to increase national rice production is quite large. To increase productivity on this land as a source of rice production takes the right technology. One of the technologies are cheap and easy to implement is the use of farmers' varieties. Dry season rice farming with production of 5 ton gkg / ha provide value gain on cash and total costs amounted to Rp 10.200.000, with B / C ratio of 2.12. While the benefits of farming in the rainy season with production of 3 ton gkg / ha amounted to Rp 5,387,500 with B / C ratio of 1.49. Thus the introduction of improved varieties to increase productivity and farmers' income. This paper is a review of some literature research results aim to provide information in improving rice productivity and farmer incomes by introducing new varieties of rice.